2019
DOI: 10.1002/aelm.201900347
|View full text |Cite
|
Sign up to set email alerts
|

High‐Transconductance Stretchable Transistors Achieved by Controlled Gold Microcrack Morphology

Abstract: healthcare applications and robotics. [5][6][7] Organic electrochemical transistors (OECTs) are the building blocks of many of the most sensitive sensors. [8,9] Unlike conventional field effect transistors (FETs), OECTs consist of an active layer with mixed electronic and ionic transport, enabling remarkably high transconductance (g m ) for high amplification of signals. [10,11] For example, OECT-based devices for electrophysiological recording with high signal integrity, [8,9,12] highly sensitive biosensors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 66 publications
2
102
0
Order By: Relevance
“…Here, the strain causes uniform microcracks in the metal thin film (Figure 1b‐II), forming a percolating network that serves as the pathway for electron transfer. [ 84–86 ] Two factors influence the stretchability of the metal film. The first factor corresponds to the local strain concentrating sites.…”
Section: Principles Of Stretchable Electronics Based On Pdms Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the strain causes uniform microcracks in the metal thin film (Figure 1b‐II), forming a percolating network that serves as the pathway for electron transfer. [ 84–86 ] Two factors influence the stretchability of the metal film. The first factor corresponds to the local strain concentrating sites.…”
Section: Principles Of Stretchable Electronics Based On Pdms Substratesmentioning
confidence: 99%
“…Because of the soft property of the PDMS substrate and weak metal film/PDMS interface adhesion, the PDMS substrate allows the percolating network structure to deform out of the plane by deflecting and twisting; thus, the strain in the film is further dissipated. [ 84,86 ] Inspired by this mechanism, carbon nanotubes (CNTs) have also been deposited on the surface of PDMS to fabricate stretchable electrodes or strain sensors. [ 87–89 ] The weak connecting points among the nanowires can serve as local strain concentrating sites.…”
Section: Principles Of Stretchable Electronics Based On Pdms Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the e-Ag NPs effectively preserve the electrical pathway under strain. [39,40] On the other hand, when the stress was released, the micro-fibril perfectly recovered to its initial state ( Figure 3F). Therefore, it can be concluded that the Janus-faced electrode effectively maintains the percolation network of e-Ag NPs even in the stretched state as well as its electrical performance after repeated deformations.…”
Section: Understanding the Behavior Of E-ag Nps Under Strainmentioning
confidence: 99%
“…Furthermore, neuro-inspired computational platforms made by OECTs interfaced with cellular systems, [205,206] integrated ionic-based logic gates including inverters and NAND gates [124,188] and stretchable synaptic OECTs [48] were also developed, which expand the functionality boundaries of the current neuromorphic devices. In general, the easily tailored features and continuously tunable conductance range reported in various organic materials and architectures for OECTs have demonstrated great perspective for neuromorphic computing applications.…”
Section: Memory and Neuromorphic Devicesmentioning
confidence: 99%